Implementation of the Visual, Auditory, and Kinesthetic (VAK) Learning Model Assisted by E-Flashcard Media to Improve Elementary School Students' Beginning Reading Skills - Firra Dwi Nur’Ani; Neneng Sri Wulan; Wulan, Hisny Fajrusalam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research is motivated by the low initial reading ability of second-grade students at SDN 1 Nagrikidul. One of the solutions to address this issue is by using the Visual, Auditory, and Kinesthetic (VAK) learning model aided by e-flashcard media. This study aims to improve the beginning reading skills of students in the second grade at SDN 1 Nagrikidul, which consists of 25 students, with 15 girls and 10 boys. The research method used is classroom action research (CAR) conducted in two cycles. Each cycle consists of 1 meeting and four stages of learning, namely: planning, implementation, observation, and reflection. The research was conducted in December 2024. The data collection techniques included documentation and observation. Data analysis involves qualitative data analysis techniques. The assessment instruments consist of observation sheets for learning activities and student activity sheets. Based on the results of data analysis, the initial reading ability of second-grade students at SDN 1 Nagrikidul in the pre-cycle was obtained with an average of 41%. In Cycle I, the average score increased by 88%. In cycle II, there was a significant increase of 100% with 25 students achieving mastery. It can be concluded that the application of the visual, auditory, and kinesthetic (VAK) learning model assisted by e-flashcard media can improve the initial reading skills of second-grade students at SDN 1 Nagrikidul.